Fuel poverty in Ireland: An analysis of trends and profiles - Arya Pillaia; Miguel Angel Tovar Rea\~nos; John A. Curtis (The Economic and Social Research Institute (ESRI), 2022)
Fuel poverty in Ireland is a significant issue faced by almost a quarter of the population as per government statistics. In this study, we investigate the trends in fuel poverty in Ireland between 2008 and 2020 using the Irish subset of EU SILC data. We find that the increase in the proportion of households receiving fuel allowance and the decrease in the proportion of poor-quality dwellings have a significant positive impact on the decline in aggregate fuel poverty experienced. We also analyse a sample of low-income households that experience fuel poverty and compare groups that are targeted by official policies with others on key indicators. We find that the existing supports normally target lower-income households who live in energy-inefficient dwellings and are of retirement age. We also find that non-targeted larger urban families who live in rented or mortgaged dwellings experience significant fuel poverty due to difficulty paying bills. We identify some gaps in the current policies that target fuel poverty. We propose that the existing policies in Ireland targeting fuel poverty should be expanded to effectively reduce fuel poverty in Ireland.
Keywords: 330; Fuel poverty; energy-efficient retrofits; policy evaluation